Lilian Davidson (“Ulick Burke”) and Jennifer Davidson (“Jennifer Maude”): Mistaken Identities and Short-Lived Success in the Irish Theatre of the 1930s - José Lanters (Estudios Irlandeses)
In January 1931, the Dublin Gate Theatre produced the three-act tragedy Bride by “Ulick Burke”, pseudonym of Lilian Lucy Davidson (1879-1954), who was already known in Dublin as a painter and art teacher. The play’s script does not survive, and Davidson’s other excursions into writing were sporadic. A comprehensive essay about her life and career by Katherine Cahill published in 1999 misattributes some written works to her while omitting others. Various other publications perpetuate these mistakes and erroneously credit her with co-founding the Torch Theatre Company in Dublin in 1935, under the name “Jennifer Maude”. However, that credit should go instead to Jennifer Davidson (1909-1993), who acted at the Torch Theatre under that pseudonym and took out a patent for the theatre, which closed its doors in 1937. This article aims to set the record straight and to throw light on the achievements of both Miss Davidsons at an uncertain time for women in Irish public life. Looking at their precarious careers and their connections with each other and with people associated with the Abbey, Gate, Queen’s, and Torch theatres also reveals the intimate relations that existed between the various entities that made up the Dublin theatre world of the 1930s.